Ductility enhancement of autoclaved cellulose fiber reinforced cement boards manufactured using a laboratory method simulating the Hatschek process. (15th March 2017) - Akhavan, Alireza; Catchmark, Jeffrey; Rajabipour, Farshad
Highlights: Ductility of FC boards can be altered by modifying the cementitious matrix mixture. Reducing the density of the FC board is an effective method to increase ductility. Replacing cement with fly ash increases the ductility and reduces the matrix strength. Replacing fly ash with silica quartz reduces the ductility. Fiber mineralization was not observed in autoclaved FC boards. Abstract: Autoclaved fiber cement (FC) boards manufactured using the Hatschek process are commonly used as building products such as siding and shingles. Despite their advantages, these products may exhibit low ductility and volume instability. A common, yet expensive, method for improving ductility is increasing the fiber content. In this study, a procedure to manufacture FC boards in the laboratory was introduced, and alternative economical methods for increasing the boards' ductility were investigated. Ductility was measured using a 3-point or 4-point bending tests, while the microstructure of the boards was studied using scanning electron microscopy. The results show that ductility of FC boards was improved by reducing their matrix tensile strength. This was achieved by reducing the density (increasing porosity) of FC boards or by partially replacing Portland cement with fly ash. Fiber mineralization was not found to be the cause of brittleness in the investigated FC boards.